Pemanfaatan Media Interaktif pada Pembelajaran Matematika di Sekolah Dasar - Mey Prihandani Wulandari; Nur Anida Zahroh; Putik Rahayu; Shiva Putri Elvitriana (Journal of Research in Education & Technology, 2025)
The purpose of this study is to present a review of various studies related to the development of interactive learning media, especially in the context of mathematics learning in elementary schools. By referring to the table containing 12 Sinta indexed articles and 3 Scopus indexed articles, this study identified and analyzed eight relevant studies, covering various methods and media, such as interactive multimedia, animated videos, and educational games. These studies show the effectiveness of using learning media in improving students' understanding of mathematical concepts and problem-solving abilities. Through various approaches, such as MDLC (Multimedia Development Life Cycle) and role-playing, the results of this study provide valuable insights into how technology can be integrated into learning to create a more engaging and effective learning experience. These findings highlight the importance of developing innovative learning media to support the education process in the digital era.